Søren Kierkegaard-litteratur 1971 -1980: Tilføjelser til bibliografien i Kierkegaardiana XII 1982, pp. 129-235 - Jørgensen, Aage (KIERKEGAARDIANA, 1988)
Søren Kierkegaard-litteratur 1971 -1980 Tilføjelser til bibliografien i Kierkegaardiana XII 1982, pp. 129-235